Optimizing the Distribution of Sub District Infrastructure Supporting Capacity on Economic Growth in West Halmahera District - Bakri Soamole; Prince Charles Heston Runtunuwu (AIBPM Publisher, 2020)
Basic fundamentals of economic development starting from the distribution of road infrastructure, clean water, electricity and telecommunications networks have an effect on economic growth in West Halmahera Regency. Does the distribution of infrastructure affect Economic Inequality in West Halmahera Regency. Another cause is the geographical condition of the districts in North Maluku, which are separated from islands. This requires a large amount of time and budget so that districts / cities can carry out road infrastructure development more optimally. the level of income inequality in districts in West Halmahera Regency in 2017 was 1.055. Based on the criteria that have been determined in the Williamson index analysis, it can be said that the inequality in West Halmahera Regency, Jailolo District in 2017 is relatively small. It can be seen in the table above that from 2017, the value of inequality has not changed, namely 1.055 is still relatively small.